Decision of Judges on Proof of Narcotics Rised for the State - Andy Pranomo (Pancasila and Law Review, 2020)
Pancasila as the source of state law, the placement of Pancasila as the source of all sources of state law is in accordance with the Preamble of the 1945 Constitution of the fourth paragraph, namely Almighty Godliness, Just and Civilized Humanity, Indonesian Unity, Democracy Led by Wisdom in Consultation and / Representative, and Justice for All Indonesian People. The position of Pancasila is the basis and ideology of the state as well as the philosophical basis of the state so that any material contained in the laws and regulations must not conflict with the values of Pancasila. Pancasila can be applied in everyday life, in this case the values of Pancasila can be seen in the role of the prosecutor in the execution of narcotics crimes at the Metro District Attorney's Office, which is more dominant as a factual role, because it is based on the fact that the prosecutor who carried out narcotics evidence was confiscated for state, law enforcement by judges on evidence of narcotics in the Metro District Court Decision. In his consideration that the evidence presented by the public prosecutor before the court and confirmed by the defendant is a tool or object used in the crime. Narcotics, which refers to Article 101 paragraph (1) of Law Number 35 of 2009 concerning Narcotics, explains “Narcotics, Narcotics Precursors and tools or goods used in Narcotics and Narcotics Precursors or related to narcotics and Narcotics precursors. The role of the prosecutor in executing booty from narcotics crime at the Metro District Attorney is more dominant as a factual role, because it is based on facts, namely the prosecutor executed based on the Metro District Court Decision Number: 132/Pid.Sus/2015/PN.Met. Then the factors inhibiting the prosecutor in executing booty from the crime of narcotics at the Metro District Attorney are: Obstacles in executing narcotics evidence confiscated for the State, namely juridical and nonyuridical obstacles. The purpose of this research is to understand how the judge's verdict on narcotics evidence is confiscated for the state. The research method used is the Normative and Empirical methods.